Lexico-semantic features of technical teams of English and Uzbek languages. - KHUSENALIYEVNA, KADIROVA DILFUZA; CHORIYEVNA, ALMARDANOVA ZULFIYA; ORAKBAYEVNA, KAIPBERGENOVA DILBAR (The journal of contemporary issues in business and government, 2021)
This article examines the integral and differential features of technical terms when they are translated from English to Uzbek. Currently, adequate translation of texts containing English technical terms that are introduced into the terminological system based on cognitiveness is considered the most difficult and urgent task, since these language units acquire new semantic features in the thermosystem. As a result, this article emphasizes the importance of creating a bilingual (Anglo-Uzbek) dictionary of technical terms.